The Relationship Between the Range of Hip Rotation and the Quadriceps Angle in Subjects With and Without Flat Foot - Lee, Keun-hyo; Chon, Seung-chul (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2018)
Background: Alignment of the lower limb is an important factor, influencing balance and gait in kinematics and kinetics, in patients with and without a flat arched foot. Flat arched foot are associated with the range of motion (ROM) of the hip and alignments of the knee joints, is strongly influenced. Objects: The purpose of this research was to investigate the relationship between hip joint ROM and quadriceps angle (Q-angle), by dividing them into two groups according to the presence or absence of flat feet, using a navicular drop test (NDT) and resting calcaneal stance position (RCSP). Methods: Forty elderly patients were allocated to the experimental group (flat foot group, n1=20) or the control group (non-flat group, n2=20). Universal and digital goniometer, tractograph and tape measure were used to determine the related changes in the hip ROM, Q-angle, NDT and RCSP. Results: Data were analyzed using the Pearson correlation coefficients. Active internal ROM of the hip joint (right, r=.803, p<.001), (left, r=.951, p<.001) were highly correlated with NDT, and also, was moderately correlated with Q-angle (right, r=.562, p=.019), (left, r=.757, p<.001). Passive internal ROM of the hip joint (right, r=.742, p=.001), (left, r=.922, p<.001) were highly correlated with NDT, and also, was moderately correlated with RCSP (right, r=-.530, p=.029) and with Q-angle (right, r=.710, p=.001), (left, r=.698, p=.002) in the flat foot group. However, no strong correlation among the hip ROM, NDT, RCSP and Q-angle were found in the non-flat foot group. Conclusion: This research may provide evidence of the correlations between hip internal ROM and flat foot. KCI Citation Count: 0